Non-invasive Early Prediction of Septic Acute Kidney Injury by Doppler-Based Renal Resistive Indexes Combined With Echocardiographic Parameters: An Experimental Study - Zhang, Ying; Zhu, Jianing; Zhang, Chuyue; Xiao, Jing; Liu, Chao; Wang, Shuo; Zhao, Ping; Zhu, Yaqiong; Wang, Li; Li, Qiuyang; Luo, Yukun (Frontiers in Medicine, 2021)
Noninvasive early prediction of septic acute kidney injury (S-AKI) is still urgent and challenging. Increased Doppler-based renal resistive index (RRI) has been shown to be associated with S-AKI, but its clinical use is limited, which may be explained by the complex effects of systemic circulation. Echocardiogram allows noninvasive assessment of systemic circulation, may provide effective supplement to RRI. To find the value of RRI combined with echocardiographic parameters in the noninvasive early prediction of S-AKI, we designed this experiment with repeated measurements of ultrasonographic parameters in the early stage of sepsis (3h, 6h, 12h, 24h) in cecum ligation and puncture (CLP) rats (divided into AKI and non-AKI group at 24h based on serum creatinine), with sham-operated group served as controls. Our results found that RRI alone could not effectively predict S-AKI, but when combined with echocardiographic parameters (heart rate, left ventricular end-diastolic internal diameter, left ventricular end-systolic internal diameter), the predictive value was significantly improved, especially in the early stage of sepsis (3h, AUC: 0.948, 95% CI 0.839-0.992, P<0.001), and far earlier than the conventional renal function indicators (serum creatinine and blood urea nitrogen), which only significant elevated at 24 h. Our method showed novel advances and potential applications in early detection of S-AKI.